HORIZONTAL AND VERTICAL LOOPS GEOTHERMAL HEATING SYSTEM - Komilov, O.S.; Sayfulloev, S.S. (Educational Research in Universal Sciences, 2024)
This article provides a detailed exploration of two fundamental configurations in geothermal heat pump systems-horizontal loops and vertical loops. Offering insights into their distinct layouts, efficiencies, and applications, the content provides a comparative analysis to guide readers in choosing between the two configurations. With a focus on practical considerations and benefits, this article equips readers with valuable knowledge to make informed decisions when implementing geothermal heating and cooling systems.